Suppression by Derepression in Threonine Dehydratase-Deficient Mutants of Bacillus subtilis - Vapnek, Daniel (1971)
Partial suppressors of isoleucine-requiring mutants (Ile(−)), deficient in threonine dehydratase (TD), were studied. The suppression enables these auxotrophs to grow on the precursors homoserine or threonine as well as isoleucine. There are two genetically distinct classes of these suppressors: sprB, linked to threonine mutational sites, and sprA which is not linked to the Ile or Thr genetic region. SprA leads to the appearance of a low level of TD activity (2 to 4% of wild type) compared to <0.2% in Ile(−) mutants. This new TD activity is not activated by glutathione or adenosine monophosphate. Unlike the major TD, it is insensitive to inhibition by isoleucine and it is not coordinately controlled with dihydroxy acid dehydratase. Another class of auxotrophs, containing no suppressor mutation, can grow on isoleucine and homoserine or threonine because they possess structural gene mutations located near the terminus of the TD gene that result in partial impairment of TD. This TD activity (2% of wild type) is end product inhibited by isoleucine to a lesser extent than wild type TD. In this and a following paper, evidence is presented that sprA acts by derepressing a minor TD activity encoded within the threonine synthetic region. The major TD gene is separated from the region encoding the enzymes of threonine biosynthesis by 73% of the chromosome. Like the major TD, the minor TD catalyzes the first reaction in the conversion of threonine to isoleucine and is therefore closely related biochemically and genetically to the enzymes of the threonine synthetic region.